ID Card Printing Time Prediction With Mean Absolute Error in Linear Regression - Fawwazrin, Akmal Mugni; Arbansyah, Arbansyah; Amin Rezaeipanah (JSE Journal of Science and Engineering, 2025)
The Population and Civil Regrestration Center, know in Indonesia as the Dinas Kependudukan dan Catatan Sipil (Dukcapil), is a government agency responsible for managing and recording population data in specific regions. Dukcapil is responsible for recording births, deaths, marriages, divorces, and documenting identities through the Electronic Resident Identity Card (E-KTP). Dukcapil faces the need to address delays in document issuance, which will be the focus of this research. The data were collected directly when researchers conducted Praktek Kerja Lapangan (PKL) at Dukcapil. This study utilizes the linear regression method to estimate the time required for printing E-KTP cards that will be produced and calculates the Mean Absolute Error (MAE). Thorough MAE calculations using the linear regression method, researchers obtained a result of 10.2923 from the available data.